Flora marina del Parque Nacional Isla del Coco, Costa Rica, Pacífico Tropical Oriental - Fernández, Cindy (Revista de Biología Tropical, 2008)
Marine flora of Isla del Coco National Park, Eastern Tropical Pacific. A preliminary description of the marine flora around Cocos Island is presented, with base line information on ecological data to evaluate future long-term changes. Data were collected in two expeditions to Cocos Island (September 2006 and January 2007). The macroalgae were removed with a knife and preserved in a solution of buffered 4% formalin. To determine cover percent three 10 m-transects were sampled at two depths (6 and 15 m), at five sites. A total of 42 morphs were found of which 29 were identified to species level. Ten species belong to Chlorophyta (green algae), including genera with wide distribution, such as Ulva, Cladophora and Caulerpa. Six species belong to the Phaeophyta (brown algae), in two families (Sytosiphonaceae and Dictyotaceae). Rhodophyta (red algae) was the most diverse group of macroalgae at Cocos Island, with 13 species. The macroalgae cover average was 50.7 ± 27.4% at 6 m and 47.1 ± 16.1% at 15 m. The algae with greater coverage and greater distribution around the island were Cladophora sp., Dictyota sp., Polysiphonia sp. and the calcareous algae (41% of cover in some sites). Macroalgae represent a large percentage of the benthic reef environments and play important ecological roles. Rev. Biol. Trop. 56 (Suppl. 2): 57-69. Epub 2008 August 29.